A Case of Thyrotoxicosis due to Simultaneous Occurrence of Subacute Thyroiditis and Graves' Disease. (30th October 2018) - Kageyama, Kazunori; Kinoshita, Noriko; Daimon, Makoto
Abstract : Subacute thyroiditis is an inflammatory disorder of the thyroid. Graves' disease is an autoimmune thyroid disease in which thyroid hormones are overproduced. Here we present a rare case of thyrotoxicosis due to the simultaneous occurrence of both diseases. Prompt diagnosis and therapy are required to prevent complications in patients with thyrotoxicosis.